Legal Implications and Liability Issues of Artificial Intelligence (AI)–Based Corporate Decision-Making Models (American Journal of Public Diplomacy and International Studies (2993-2157), 2026)
This article provides a comprehensive analysis of the role of artificial intelligence in decision-making within corporations. Within the scope of the study, the use of AI systems in corporate governance processes, their impact on efficiency, and the resulting legal risks are examined. In particular, it addresses issues such as determining liability in cases where decisions involving AI cause harm, algorithmic errors, differences between humans and artificial intelligence, the legal consequences of decisions made by AI, and related accountability. Additionally, based on international experience, a comparative corporate analysis has been conducted, and legislative recommendations have been developed in the conclusion.